Towards ethical international research partnerships in gender-based violence research: insights from research partners in Kenya - Weber, Sanne (Violence against women, 2022)
Research with survivors of gender-based violence in low- and middle-income countries is important to improve understanding of experiences of violence and the policies that can help combat it. But this research also implies risks for survivors, such as re-traumatization, safety concerns, and feelings of exploitation. These risks are magnified if research is undertaken by researchers from high-income countries, whose positionality produces power inequalities affecting both participants and research partners. This article describes the ethical challenges of international gender-based violence research from the perspective of Kenyan researchers and organizations and identifies recommendations about how to prevent them.